Digital implantology-a review of virtual planning software for guided implant surgery. Part II: Prosthetic set-up and virtual implant planning - Tabea Flügge; Jaap Kramer; Katja Nelson; Susanne Nahles; Florian Kernen (BMC, 2022)
Abstract Background Patient- and technology-related parameters influence the successful implementation of virtual implant planning and guided implant surgery. Besides data processing and computer aided design of drill guides as described in Part I, the possibilities and limitations for prosthetic set-up and virtual implant planning are essential (Part II). Methods The following software systems were examined using two different clinical situations for implant therapy: coDiagnostiX™, DentalWings, Canada (CDX); Simplant Pro™, Dentsply, Sweden (SIM); Smop™, Swissmeda, Switzerland (SMP); NobelClinician™, Nobel Biocare, Switzerland (NC); Implant Studio, 3Shape, Denmark (IST). Assessment criteria geared towards interfaces and integrated tools for prosthetic set-up and virtual implant planning. Results A software interface for an individual virtual prosthetic set-up was provided by two systems (CDX, IST), whereas the set-up of standardized teeth was provided by four systems (CDX, SIM, SMP, IST). Alternatively, a conventional set-up could be scanned and imported. One system could solely work with the digitization of a conventional set-up for virtual implant planning (NC). Stock abutments could be displayed for implant planning, but none of the tested software systems provided tools for the design of an individual abutment. All systems displayed three-dimensional reconstructions or two-dimensional cross-sections with varying orientation for virtual implant placement. The inferior alveolar nerve could be marked to respect a minimum distance between the nerve and the planned implant. Three implant planning systems provided a library to display more than 50 implant systems (CDX, SIM, IST), one system provided 33 implant systems (SMP) and one implant system provided 4 implant systems (NC). Conclusion Depending on the used software system, there are limited options for a virtual set-up, virtual articulators and the display of a virtual prosthetic set-up. The implant systems used by the clinician is important for the decision which software system to choose, as there is a discrepancy between available implant systems and the number of supported systems in each software.